Real rank estimate by hereditary C^*-subalgebras by projections - Sudo, Takahiro (MATHEMATICA SCANDINAVICA, 2007)
In this paper we estimate the real rank of C^*-algebras by that of their hereditary C^*-subalgebras by projections.